Social Justice in a Market Economy - Sautter, Hermann; Schinke, Rolf (Goettinger Studien zur Entwicklungsoekonomik / Goettingen Studies in Development Economics, 2018)
Latin American market-oriented reforms along the lines of the Washington Consensus need to be supplemented by a number of social policies to achieve a more equitable society. While there has been considerable progress in enhancing the efficiency, much less has been made with regard to improving the social situation. Germany has a long and successful tradition of a social market economy. However, developments in recent years have shown various pitfalls in the current economic and social security systems and the need for appropriate adjustments. Therefore, Germany as well as most Latin American countries have to look for new solutions to combine social justice with economic efficiency. This volume addresses some of the most pertinent problems in this respect.